Shame and State of The Self and Its Implications for Technique - Ricci, Walter (RRNMF Neuromuscular Journal, 2021)
The author reflects on the vicissitudes of the state of the self as it unfolds during the analytical encounter. He delineates the presence and the ubiquity of shame during the interaction between patient and analyst. An important mention is given to the concept of the subject and object polarity. As such, special emphasis is given to the rapid variation of the state of the self. This requires dedicated attention to the state of the self and its awareness, regarding how invalidating shame is to both members of the dyad during their exchanges. The outcome of this attention will be the resulting lack of emotional attunement or validation during the exchange.